Enhancing Cyber-Physical System Security: A Review of Detection and Mitigation Techniques - Thandy Simanjuntak (Geviva Publisher, 2024)
The increasing sophistication of cyber threats has driven the demand for a well-trained cybersecurity workforce. Cyber Ranges have emerged as essential platforms for hands-on training, skill development, and cybersecurity research. This paper presents a comprehensive review of Cyber Ranges, focusing on their role in cybersecurity workforce development across different regions and industries. We examine global practices, existing frameworks, and standardization efforts that shape the implementation and effectiveness of Cyber Ranges. Furthermore, we analyze the challenges in designing scalable, realistic, and adaptive training environments, considering advancements in artificial intelligence (AI), gamification, and cloud-based simulations. By evaluating best practices and identifying gaps in current methodologies, this review provides actionable insights for policymakers, educators, and industry stakeholders. The findings underscore the necessity of harmonizing Cyber Range capabilities with real-world cybersecurity demands, ensuring a resilient and highly skilled workforce ready to combat emerging threats.